Value in a digital world : how to assess business models and measure value in a digital world / Francisco J López Lubián; José Esteves - López Lubián, Francisco J.
An in-depth examination of the concept of value in a digital world, an analysis of a range of digital business models and a framework for assessing the value of digital businesses. Assessing the value of traditional business was easy.